Informal Settlements and Their Relationship to Crime - Alsanea, Dr. Faisal; Alhabardi, Abdirahman (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2025)
The research addresses the issue of doping in sports from a legal perspective, highlighting the health and social risks it poses, such as harming athletes’ health and disrupting the principle of equal opportunities in competitions. Considering these risks, the Kingdom of Saudi Arabia adopts strict regulations based on international anti-doping agreements, and in 2021 issued a regulation aimed at reducing this phenomenon. The research focuses on determining the criminal liability of athletes when doping, explaining that liability is established by the mere presence of prohibited substances in players’ samples, regardless of their intention or knowledge of it. It also points to the importance of sanctions that include canceling results and withdrawing awards to achieve deterrence for anyone who dares to commit this shameful behavior. The research concludes that awareness-raising efforts must be strengthened alongside the implementation of sanctions, while developing local legislation in line with international standards. It also recommends launching rehabilitation programs for athletes and supporting international cooperation to effectively combat this phenomenon